SKRINING KESEHATAN PADA LANSIA DI SURAKARTA - Wahyu Tri Sudaryanto; Isnaeni Herawati; Wahyuni Wahyuni; Ika Yuli Ayuningrum; Bhisma Murti; Rizki Setiawan; Nuristiqomah Dwi Putri (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2023)
The care of older people has become an important issue due to increased life expectancy and improved quality of life. The escalating problem of multiple chronic conditions among elderly draws public health attention due to increasing proportion of the elderly population. Conditions such as hypertension, diabetes mellitus, stroke, cardiovascular disease, and cancer, are the leading causes of death worldwide. Periodic medical check up is an important way to reduce or control the severity of these chronic diseases in elderly people. Community-based health intervention is needed to improve awareness of continuing visit to elderly health post. The aim of this project is to conduct health screening in elderly in Surakarta. This activity is carried out on a collaboration between Study Program of Physiotherapy, Faculty of Health Sciences, Universitas Muhammadiyah Surakarta and Masters Program in Public Health, Universitas Sebelas Maret.